Emigration, internationalization, and 'Brain Drain' : propensities among British academics - Schuster, Jack H. [Verfasser] (My University, 1994)
"This research links two important higher education phenomena: potential 'brain drain' among academics abroad and the U.S. academic labor market. The inquiry draws on the 'brain drain' literature and is grounded primarily on a secondary analysis of a major survey (1989) of British university and polytechnic faculty members. The analysis shows that fully 40.0 precent of university faculty are 'seriously considering' a move abroad with the substantial majority favoring the United States as a destination. Faculty characteristics - including academic field, research versus teaching orientation, rank, age, gender, and political identification - are correlated with faculty members' professed interest in emigration. the analysis also compares (former) polytechnic to university faculty as well as to a subset of Oxford and Cambridge faculty." (author's abstract, IAB-Doku) ((en)) Auf der Grundlage der Literatur zum "Brain drain" und der Sekundäranalyse einer 1989 bei britischen Hochschullehrern durchgeführten Erhebung werden Zusammenhänge zwischen potentiellen Auswanderungsabsichten und dem Arbeitsmakrt für Hochschullehrer in den USA untersucht. Dabei werden Merkmale nach Fakultäten, Fachgebieten, Forschungs- bzw. Lehrorientierung, Rang, Alter, Geschlecht und politischer Identifizierung mit dem geäusserten Interesse an einer Auswanderung in Beziehung gesetzt. Ausserdem werden Fachhochschul- und Universitätsangehörige verglichen. (IAB)
Auswanderung, Internationalisierug und "Brain Drain" : potentiell Auswanderungsabsichten bei britischen Hochschullehrern
Keywords: P 3.2.3 Lehrer; G 1.3.3.3 Mobilität; G 2.4 Sozialer Wandel; G 2.4.4 Biografiegestaltung; I 2.2.1 Westeuropa; Brain drain; Lehrer; Hochschullehrer; Berufsproblem; Universität; Fachhochschule; Auswanderung; Lebensalter; Geschlecht; Politische Einstellung; Beruflicher Status; Arbeitsmarktchance; Quantitative Angaben; Großbritannien